The Political Economy of Regionalism - Söderbaum, F. author. aut Link
XX, 251 p.
Keywords: The Political Economy of Regionalism: The Case of Southern Africa challenges prevailing wisdom, showing how ruling political elites and 'big business' join forces with certain external actors in order to promote market integration and economic globalization, boost regimes, and to satisfy group-specific and even personal interests. Only rarely do these forms of regionalism contribute to the poor and disadvantaged, who instead opt out, and survive through informal economic regionalisms or seek to create regionalisms rooted in civil society.